2005
DOI: 10.1007/s00464-005-3002-4
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain relief after laparoscopic cholecystectomy: A placebo-controlled double-blind randomized trial of preincisional infiltration and intraperitoneal instillation of levobupivacaine 0.25%

Abstract: The combination of preincisional local infiltration and intraperitoneal instillation of L-B 0.25% shows an advantage for postoperative analgesia after laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 19 publications
5
74
1
1
Order By: Relevance
“…It occurs after diaphragmatic stretching with phrenic nerve neuropraxia. The incidence of shoulder pain is markedly lower in laparoscopic hysterectomy when compared to laparoscopic cholecystectomy [25]. In our study, shoulder tip pain was observed only in 2 patients in group R and none in group RD.…”
Section: Discussionmentioning
confidence: 55%
“…It occurs after diaphragmatic stretching with phrenic nerve neuropraxia. The incidence of shoulder pain is markedly lower in laparoscopic hysterectomy when compared to laparoscopic cholecystectomy [25]. In our study, shoulder tip pain was observed only in 2 patients in group R and none in group RD.…”
Section: Discussionmentioning
confidence: 55%
“…[53] It occurs after diaphragmatic stretching with phrenic nerve neuropraxia and reported after laparoscopic cholecystectomy is markedly lower than that reported after gynecologic laparoscopy. [53][54][55] We found a low incidence of shoulder pain in all treatment groups, because the residual intraperitoneal CO 2 was carefully removed by the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Local anesthetic or NSAID infiltration as a part of multimodal analgesia is performed to decrease the pain after surgery. Incision-site local anesthetic infiltration has been found to be effective for the management of postoperative pain, especially in radical prostatectomy and laparoscopic cholecystectomy (18,19). However, our literature search did not reveal any study related to the effect of wound infiltration with lornoxicam alone in thyroid surgery.…”
Section: Discussionmentioning
confidence: 77%